Comprehensive Framework for the Application of Bio Composites Materials in Sustainable Manufacturing - Fatchurrohman, Nanang; Yetrina, Mutiara (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
The development of bio-composites, known for their environmental benefits and versatility, is being increasingly explored as various industries seek eco-friendly alternatives to traditional materials. The article presents a comprehensive discussion for incorporating bio-composites into manufacturing operations using sustainable practices. Through the exploitation of renewable resources and green production processes, manufacturers can increase the sustainability, durability, and strength of bio-composites. The system emphasizes the importance of maximizing resource utilization, minimizing waste, and minimizing environmental impact throughout the production process. The results of this research confirm that the application of bio-composites in green manufacturing has a range of important competitive advantages. It encompasses minimizing environmental footprint, promoting resource efficiency, fostering innovation, and ensuring flexibility. Furthermore, this research demonstrates that the application of bio-composites not only enables the achievement of environmental sustainability and resource efficiency goals but also enhances product performance and market positioning, thereby delivering substantial competitive advantages in a dynamic market. The relevance of this study lies in its comprehensive and interdisciplinary contribution to sustainable manufacturing. This research is among the limited studies that provide a comprehensive lifecycle model, encompassing sourcing and production, quality assurance, distribution, and customer satisfaction, designed explicitly for bio-composites.